Dampak PSBB dan PSBB Transisi di DKI Jakarta dalam Pengendalian COVID-19 - Hermawan Saputra; Nadilah Salma (Faculty of Public Health, Hasanuddin University, Makassar, 2020)
The COVID-19 pandemic has negative impacts on various sectors so that Government wisdom in determining evidence-based intervention priorities becomes very important. DKI Jakarta Regional Government has chosen the Transitional PSBB policy as an effort economy relaxation but how effective the policy is in controlling COVID-19. The research finds out the impact of the implementation of the PSBB and Transitional PSBB (Large-Scale Social Restrictions) in DKI Jakarta as well as the health system capacity in the context of handling and controlling COVID-19. This is a qualitative study using desk research and expert studies on PSBB and its implementation. The case situation in this study uses the period during which the Jakarta PSBB and Transitional PSBB was implemented from 10 April-30 July 2020. The incidence rate and positivity rate of COVID-19 increased along with the implementation of the Transitional PSBB. In terms of the mobility of the people of DKI Jakarta, there has been an increase in public places, workplaces, shopping centers and a decrease in mobility in residences and parks when compared to the implementation of the PSBB. It was also found that the capacity of the health system was still low, including the health infrastructure, facilities, and health human resources. The easing of the PSBB is implemented too early so it is ineffective and counterproductive to the efforts to handle and control COVID-19 that DKI Jakarta has been working on so far. It is necessary to formulate a concrete strategy for promotive and preventive mainstreaming, by involving Public Health Experts.